2015
DOI: 10.1016/j.patrec.2015.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Speeding up the cyclic edit distance using LAESA with early abandon

Abstract: The cyclic edit distance between two strings is the minimum edit distance between one of this strings and every possible cyclic shift of the other. This can be useful, for example, in image analysis where strings describe the contour of shapes or in computational biology for classifying circular permuted proteins or circular DNA/RNA molecules.The cyclic edit distance can be computed in O(mn log m) time, however, in real recognition tasks this is a high computational cost because of the size of databases. A met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In many real-world applications, such as in bioinformatics [4,22,25,7] or in image processing [3,33,34,32], any cyclic shift (rotation) of P is a relevant pattern, and thus one is interested in computing the minimal distance of every length-m substring of T and any cyclic shift of P , if this distance is no more than k. This is the circular pattern matching with k mismatches (k-CPM) problem. A multitude of papers [17,8,6,5,9,24] have thus been devoted to solving the k-CPM problem but, to the best of our knowledge, only average-case upper bounds are known; i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many real-world applications, such as in bioinformatics [4,22,25,7] or in image processing [3,33,34,32], any cyclic shift (rotation) of P is a relevant pattern, and thus one is interested in computing the minimal distance of every length-m substring of T and any cyclic shift of P , if this distance is no more than k. This is the circular pattern matching with k mismatches (k-CPM) problem. A multitude of papers [17,8,6,5,9,24] have thus been devoted to solving the k-CPM problem but, to the best of our knowledge, only average-case upper bounds are known; i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The CPM problem can also be solved in O(n) time [15]. Applications where circular strings are considered include the comparison of DNA sequences in bioinformatics [24,4] as well as the comparison of shapes represented through directional chain codes in image processing [37,36]. In both applications, it is not sufficient to look for exact (circular) matches.…”
Section: Introductionmentioning
confidence: 99%
“…As of the NN algorithm bottleneck, the main issue of this classifier is that no To our best knowledge, the only formal study with a similar idea focusing on string data is found in the work by Palazón-González and Marzal [20], in which 115 the Linear Approximating and Eliminating Search Algorithm (LAESA) [21] Fast Similarity Search method is combined with some distance bounds for the case of the cyclic edit distance. In our work, we further explore this idea of distance bounds generalizing the data representation considered to sequences of vectors, instead of exclusively examining string data, and thus obtaining remarkable 120 reductions in terms of time consumption.…”
mentioning
confidence: 99%